Workflow net possibilística para problemas de não conformidade em processos de negócios - Rezende, Leiliane Pereira de (2013)
Contemporary organizations use information technology to support activities and possibly automate processes due to its complexity and variety. Systems Business Process Management significantly influence the way companies organize work, besides forcing them to adjust their business processes to them, allowing the occurrence of various problems. One of the principal is the incompatibility between the preferred way of the work of company employees and the way the system process management organizes the sequencing of activities, forcing them to work very often "outside the system" by running business processes "inadequate" compared to the model set by the management system. The objective of this work is to propose a new model of the business process based on WorkFlow nets and on possibilistic Petri nets". The routing patterns in existing business processes are modeled by WorkFlow nets, and to express in a more realistic way the uncertainty attached to human activities, possibilistic Petri nets" with uncertainty on the marking and on the transition firing are considered. The proposed approach focuses on flexibility by deviation from the perspective of the control flow and is able to deal with the inconsistencies between the process model and the execution, generated by human actors. The process Service Complaint", where human actors are involved in the process activities, and two examples of deviations arising from the control flow are used to illustrate the approach. The markings and firings uncertain allow deviate so that no blockage occurs in the state of the process and the model is not changed. The advantage of this approach is the maintenance of good properties in the model of the process, because the "classical Petri nets" is not modified; therefore the classical methods for analyzing processes remain valid. Furthermore, through the defuzzification of knowledge, it is possible to formalize the deviation through the sequence of activities that have not been executed, but should have been.